Fuzzy-PI Torque and Flux Controllers for DTC with Multilevel Inverter of Induction Machines - N. M. Nordin; N. R. N. Idris; N. A. Azli; M. Z. Puteh; T. Sutikno (Institute of Advanced Engineering and Science, 2014)
In this paper the performance of flux and torque controller for a Direct Torque Control of Cascaded H-bridge Multilevel Inverter (DTC-CMLI) fed induction machines are investigated. A Fuzzy-PI with fixed switching frequency is proposed for both torque and flux controller to enhance the DTC-CMLI performance. The operational concepts of the Fuzzy-PI with the fixed switching frequency controller of a DTC-MLI system followed by the simulation results and analysis are presented. The performance of the proposed system is verified via MATLAB/Simulink©. The proposed system significantly improves the DTC drive in terms of dynamic performance, smaller torque and flux ripple, and lower total harmonic distortion (THD).DOI: http://dx.doi.org/10.11591/ijpeds.v5i2.6581